2020
DOI: 10.1186/s13063-020-04773-6
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Famotidine in improvement of outcomes in Hospitalized COVID-19 Patients: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives This study aims to investigate the effect of Famotidine on the recovery process of COVID-19 patients. Trial design This phase III randomized clinical trial was designed with two parallel arms, placebo-controlled, single-blind, and concealed allocation. Participants All COVID-19 patients admitted to Shahid Mohammadi Hospital in Bandar Abbas whose PCR test results are positive for SARS-Cov-2 and sign the written consent of the study are included in the study and immunocompromised patients, end-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…In contrast, study NCT04370262 administers intravascular famotidine doses that are more than 20-fold greater than the IC 50 for antagonism of H 2 . Other prospective randomized clinical studies involving high dose famotidine for treating COVID-19 are in progress [ Samimagham et al (2020) , NCT NCT04504240]. The data presented herein provides a rationale for famotidine dose selection to maintain a steady state concentration at a reasonable multiple of the IC 50 for systemic antagonism of H 2 and indicate that oral tablet dosages of between 40 mg every 8 h to 80 mg every 8 h should be sufficient to insure maximal H 2 target effects.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, study NCT04370262 administers intravascular famotidine doses that are more than 20-fold greater than the IC 50 for antagonism of H 2 . Other prospective randomized clinical studies involving high dose famotidine for treating COVID-19 are in progress [ Samimagham et al (2020) , NCT NCT04504240]. The data presented herein provides a rationale for famotidine dose selection to maintain a steady state concentration at a reasonable multiple of the IC 50 for systemic antagonism of H 2 and indicate that oral tablet dosages of between 40 mg every 8 h to 80 mg every 8 h should be sufficient to insure maximal H 2 target effects.…”
Section: Discussionmentioning
confidence: 92%
“…This early double blind randomized clinical trial involved high intravenous famotidine doses in combination with either hydroxychloroquine or remdesivir ( ClinicalTrials.gov Identifier: NCT04370262), but that trial has been delayed and is yet to complete enrollment or report results. HD famotidine for treatment of COVID-19 is now also being clinically tested in Bangladesh ( ClinicalTrials.gov Identifier: NCT04504240), and Iran ( Samimagham et al, 2020 ). Recent encouraging clinical reports include simultaneous administration of famotidine and cetirizine at standard OTC doses ( Hogan et al, 2020 ) and HD famotidine with celecoxib ( Tomera and Kittah, 2020a ; Tomera and Kittah, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…As for non-hospitalized patients, another study showed improvements of disease symptoms after starting high dose oral famotidine [ 42 ]. Two phase III clinical trials have been initiated to investigate the clinical efficacy of famotidine on the recovery process of COVID-19 patients [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…in both arms [ 78 ]. A study protocol for a further trial has been published [ 79 ]. This trial examined the effect of standard treatment alone or standard treatment plus p.o.…”
Section: Further Publications Since the Time Of Submissionmentioning
confidence: 99%